Relationship of fitness combine results and national hockey league performance: A 25-year analysis - Cohen, J. N.; Thompson, K. M.; Jamnik, V. K.; Gledhill, N.; Burr, J. F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Along with past performance, professional teams consider physical fitness and physiological potential in determining the value of prospective draft picks. The National Hockey League (NHL) Combine fitness results have been examined for their ability to predict draft order, but not bona fide hockey performance. Therefore, we sought to identify the relationships of combine fitness test results to short- and long-term NHL performance. Methods: During NHL Combine fitness testing (1994-2007), a standardized battery of tests was conducted. Player performance (1995-2020) was quantified using career cumulative points, time on ice, transitional period to playing in the NHL, and NHL career length. Forward and defensive positions were considered separately. Goalies were not considered. Stepwise linear regression analysis was used to identify fitness variables that predict NHL success. Results: Overall models ranged in their predictive ability from 2% to 16%. The transitional period was predicted by peak leg power and aerobic capacity (VO2max; forwards, R2 = .03, and defense, R2 = .06, both P < .01). Points and time on ice within seasons 1 to 3 were predicted by peak leg power and VO2max for forwards and defense (R2 = .02-.09, P < .01). Among players accumulating 10 NHL seasons, cumulative points were inversely related to upper-body push-strength-related variables in forwards (R2 = .11) and defense (R2 = .16; both P < .01). Conclusions: The NHL Combine fitness testing offers meaningful data that can inform the likelihood of future success. Peak leg power and VO2max predict league entry and early career success. Counterintuitively, upper-body strength is inversely related to long-term performance, which may offer insight into recruitment strategies, player development, or differential team roles.